Economic Impact of Tourism Finance in Nepal - Gautam, Bishnu Prasad (NRB Economic Review, 2008)
This paper investigates the effects of tourism industry on gross domestic product (GDP) and finds a significant positive relationship between tourism financing and GDP. Moreover, the role of various sources of tourism financing, including government financing and the loan financing of banks and financial institutions, on economic growth has also been examined and the result supports the conventional wisdom that there is significant positive relationship between the variables. This paper uses primary data collected from the field survey during February - April 2006 and the secondary data utilizing 30 annual observations from FY 1974/75 to 2004/05. Both the level and logarithmic form data are examined using the OLS estimation method and the Cochrane-Orcutt (C-O) iterative procedure is applied considering the robustness of the model.